Pelatihan Perakitan Dan Pemrograman Robot Berbasis Mikrokontroler - Direstu Amalia; I Gusti Agung Ayu Mas Oka; Viktor Suryan; M. Indra Martadinata; Rio Rizko; Randa Agusta Pratama; Jhellyananda Putri (Jurnal Pengabdian Kepada Masyarakat (JPKM) Langit Biru, 2023)
Arduino is well-known to robot enthusiasts in general and is used by students to professionals. This community service activity is intended as an implementation of the field of airport engineering technology which is expected to provide increased skills that can become provisions in the world of work for training participants. This activity was carried out for 1 (one) day using an approach of 30% theory and 70% practice. Participants are guided to do independent practice and given a pre-test and post-test to see the progress of the participant's understanding of the material provided.